THE PERFORMANCE OF CIVIL SERVANTS WITH JOB SATISFACTION AS A MEDIATOR: THE PERFORMANCE OF CIVIL SERVANTS WITH JOB SATISFACTION AS A MEDIATOR - Misriyani, Sri; Supeno, Bambang; Burhan, Burhan (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
This study aims to address the performance issues of the State Civil Apparatus (ASN) in Rokan Hulu Regency, despite ongoing bureaucratic reforms. The phenomenon of suboptimal ASN performance, particularly in key sectors like health, education, and infrastructure, indicates a gap in leadership effectiveness and job satisfaction. The purpose of this research is to explore the impact of inspirational leadership on ASN performance, with job satisfaction as a mediating variable. A quantitative research method was employed, using a descriptive approach with a sample of 368 employees. Data processing was conducted using PLS-SEM to test the hypothesized relationships. The results reveal that inspirational leadership significantly affects job satisfaction, which in turn positively influences ASN performance. However, inspirational leadership does not have a direct effect on performance, highlighting the importance of job satisfaction in mediating this relationship. This study provides insights into how leadership and job satisfaction contribute to enhancing ASN performance, offering practical recommendations for improving public sector management.